2022
DOI: 10.1021/acsomega.1c06442
|View full text |Cite
|
Sign up to set email alerts
|

Protecting Light Metal Alloys Using a Sustainable Plasma Electrolytic Oxidation Process

Abstract: Low-density metals such as Mg and Al (and their alloys) are of high interest for lightweight engineering applications in various industries. Moisture sensitivity, poor tribology, and corrosion susceptibility limit the direct application of these light metals. Plasma electrolytic oxidation (PEO) is extensively used to passivate light metals against corrosion and enhance their mechanical properties. PEO processes in current use are often energy-intensive and use toxic electrolytes. Incorporating composite charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…The Mg 1s spectra of FeCoMg@SHS and FeCoMgMn@SHS also supported above suggestion. Two fitted peaks were observed at binding energies of 1302.9 eV and 1303.8 eV [ 24 , 25 ], indicating the potential binding of Mg ions with silicate and other metal oxides in FeCoMg@SHS and FeCoMgMn@SHS. The Fe 2p spectra indicated that both Fe 3+ and Fe 2+ states presented in the Fe-doped SHSs.…”
Section: Resultsmentioning
confidence: 99%
“…The Mg 1s spectra of FeCoMg@SHS and FeCoMgMn@SHS also supported above suggestion. Two fitted peaks were observed at binding energies of 1302.9 eV and 1303.8 eV [ 24 , 25 ], indicating the potential binding of Mg ions with silicate and other metal oxides in FeCoMg@SHS and FeCoMgMn@SHS. The Fe 2p spectra indicated that both Fe 3+ and Fe 2+ states presented in the Fe-doped SHSs.…”
Section: Resultsmentioning
confidence: 99%